Fabrication and Characterization of Syringe Carbon Paste Electrode for Electrochemical Measurement - Anom Cahyotomo; Mohammad Jihad Madiabu; Arie Pratama Putra; Ardina Purnama Tirta; Imas Solihat; Dicky Annas (Helium: Journal of Science and Applied Chemistry, 2024)
This study aims to fabricate and characterize a syringe carbon paste electrode (SCPE) using K3Fe(CN)6 10 mM solution with cyclic voltammetry technique. Characterization is performed by varying pH (pH 4, 7, and 10) and scan rate (30 - 100 mV/s) so that the characteristics of SCPE can be observed. The K3Fe(CN)6 10 mM solution test results at various pH variations obtained the largest anodic peak current (Ipa) at pH 10 was 44.75 µA. The scan rate results at various pH showed linear results with the diffusion coefficient of 1.77 x 10-6 cm2/s, 1.65 x 10-6 cm2/s, and 2.50 x 10-6 cm2/s with r values of 0.9994, 0.9975, and 0.9992 for pH 4, pH 7, and pH 10 respectively. This indicated that a diffusion process controlled this system's mass transfer in various pH. The detection of nitrite ions at a concentration of 2 mM showed a clear oxidation peak, with the highest Ipa value of 61.28 µA in pH 7 buffer solution.